ChemInform Abstract: Hypervalent Iodine‐Catalyzed Oxidative Amidation of Methylarenes. Issue 7 (29th January 2015) - Azizi, Kobra; Karimi, Meghdad; Heydari, Akbar
Abstract The title reaction is compatible with both primary and secondary amines.